Geração e Distribuição de Riquezas no Período da Pandemia do Covid-19 - Silva, Maria da Conceição de Souza (2021)
On December 31 of 2019, China makes the first Coronavirus report to the World Health Organization (WHO). This virus quickly reached the entire world, causing effects in many social and economic aspects. The main objective of this paper is to investigate which sectors suffered considerable variations in their generation and wealth distribution during the crisis caused by the Coronavirus, based on the Statement of Value Added. This study was classified as descriptive research in terms of objectives, quantitative about the approach of the problem and documental in terms of procedures. The sample was composed by the 33 sectors available according to the B3 classification and the data were obtained from the Assaf Institute (2021). Three distinct groups were identified, the first was Group G1, which showed a decrease in wealth generation, Group G2 with stability and Group G3 with an increase. Groups G1 and G2 did not show significant differences in wealth distribution indices. In group G3 it was found that the relative participation (percentage) of employees decreased, while the relative participation of partners increased. These data suggest that, among sectors that had losses in wealth generation, the percentage of these losses was uniform, but among those sectors that had gains, only a few had results beyond the expected average.